PENGARUH PROFITABILITAS, KINERJA LINGKUNGAN, DAN UKURAN PERUSAHAAN PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Viratama, Gede Fernanda; Wirawati, Ni Gusti Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p13, 2024)
Corporate Social Responsibility (CSR) has become a major topic in the business world, where sensitivity and concern for the social environment have become fundamental for companies. CSR disclosure is a form of corporate responsibility to stakeholders. This study aims to examine the effect of profitability, environmental performance, and firm size on CSR disclosure. This research was conducted on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange and included in PROPER 2018-2020. Determination of the sample in this study using purposive sampling method. Based on this method, the number of samples used is 54 samples. The data of this study were analyzed using multiple linear regression analysis techniques. The results of this study indicate that firm size has a positive effect on CSR disclosure, profitability has a negative effect on CSR disclosure, while environmental performance has no effect on CSR disclosure. The implications of this research can prove the legitimacy theory which explains the variable size of the company where the company conducts operational activities and tries to ensure that their behavior is in accordance with the limits and norms that exist in the wider community.